ECO Friendly Mask Guide for Corona Prevention. Issue 2 (December 2020) - Tumuluru, Praveen; Raju, S. Hrushikesava; Baba, CH. M. H. Sai; Dorababu, S.; Venkateswarlu, B.
Abstract: At present, every live human being is worrying of COVID-19 and its varying forms to be attacked and its consequences. To invent the drug and vaccine, it is becoming a harder task that makes people hard to survive with this disease. Many people are getting this covid-19 because of contaminated environment as well as un-disciplinary actions. To avoid the spreading of COVID-19, the populace has to be aware with several sectors such as use of sanitizer, drinking of hot water, having of nutrition drink and hygiene food, and last but not the least consumption of immunity boosters. In this paper, we focus on developing an eco-friendly mask which not only prevents against COVID-19 but also purifies the air intake. The objective of this invention is to fight efficiently against COVID-19 pandemic in terms of preventing the spreading of Corona virus. The performance of this mask is validated against the conventional mask by considering and its maintenance will judge the success of this in the global mass society. Not only to face COVID, but also to face the pandemics to be raised in the future too. Hence, the proposed materialistic method using corona sensor will guide about corona surfaces and objects in the surrounding environment.